Analysis of the educational environment of a brazilian medical school in light of the demands of remote learning (Research, Society and Development, 2021)
The need for social distance caused impacts on medical education, which was already undergoing a process of changes. The use of remote teaching, caused by the Covid-19 pandemic, required medical schools to review educational practices and the teacher-student relationship in new scenarios. Our aim is to analyze the educational environment of an undergraduate medical course contextualizing it to the new reality, identifying aspects of the course that should be reviewed to foster the necessary transformations. Sociodemographic questionnaires and Dundee Ready Education Environment Measure (DREEM) were applied to students from the first, third and sixth years of the medical undergraduate course of a Brazilian public university from August to November 2019. The educational environment was negatively evaluated by the students, with aspects concerning motivation, inadequate use of time, encouragement of continuing education perceived as little stimulated and in need of improvement, unclear pedagogical goals and authoritarian teachers. Students' perceptions of motivation and encouragement to learn; teacher-student relationship; autonomy and encouragement to continuing education; evaluation, and feedback practice were highlighted in the data analysis. The adoption of teaching methodologies centered on the teacher does not favor the active participation of the student and does not encourage them to build knowledge. The remote modality of teaching requires a redefinition of educational practices and the places occupied by teachers and students in the teaching-learning process. Teacher improvement activities, review of teaching and assessment methods, and greater participation of students and teachers in change processes are necessary.